"Heart Appearance" Infarction of the Pons: A Case Report. (9th October 2012) - Ishizawa, Keisuke; Ninomiya, Mikiko; Nakazato, Yoshihiko; Yamamoto, Toshimasa; Araki, Nobuo
Abstract : "Heart appearance" on magnetic resonance imaging (MRI) is a unique presentation of bilateral medial medullary infarction. In contrast, "heart appearance" infarction of the pons has rarely been featured in the medical literature. In this paper, we present a case of "heart appearance" infarction of the pons with its MRI and magnetic resonance angiography (MRA) findings. The patient was an 87-year-old male who manifested with weakness in the four extremities. Later, bulbar palsy and tetraplegia became apparent, and he eventually was trapped in locked-in syndrome. Brain MRI disclosed a "heart appearance" lesion in the pons, which was high on diffusion-weighted image MRI and low on apparent diffusion coefficient map MRI. Brain MRA demonstrated that the basilar artery remained intact. A diagnosis of fresh, bilateral pontine infarction with a "heart appearance" was made. After the treatment he was transferred to another hospital for long-term care. This case suggests that bilateral ischemic involvement of the pons is possible even in the context of an intact basilar artery.